1996
DOI: 10.1002/jhet.5570330602
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of 8‐allyl‐2‐styrylchromones by the modified baker‐venkataraman transformation

Abstract: Substituted‐2‐hydroxy‐3‐allylacetophenones 2 react with cinnamoyl chlorides 3 in potassium carbonate‐acetone to give good yields of polyfunctional 1‐(2‐hydroxy‐3‐allylaryl)‐5‐aryl‐4‐pentene‐1,3‐diones 4 which exist in their enol forms 5. These on acid catalysed cyclodehydration gave 70–80% yields of substituted 8‐allyl‐2‐styrylchromones 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…This is supported by previous reports wherein 2-styrylchromones have been isolated in the enol form. [16] Consequently, the second cinnamoyl carbonyl group exists as ketone moiety, which can be attacked by a phenolate nucleophile. Elimination of water takes place during workup as a result of rearomatization.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by previous reports wherein 2-styrylchromones have been isolated in the enol form. [16] Consequently, the second cinnamoyl carbonyl group exists as ketone moiety, which can be attacked by a phenolate nucleophile. Elimination of water takes place during workup as a result of rearomatization.…”
Section: Resultsmentioning
confidence: 99%
“…[80] A similar procedure used cinnamoyl chlorides in potassium carbonate/acetone medium, and cyclodehydration occurred in the presence of concentrated sulfuric acid in ethanol at reflux (Scheme 11). [49,81] The synthesis of 3-cinnamoyl-5-hydroxy-2-styrylchromones 40 was achieved through a two-step procedure involving the condensation of 2′,6′-dihydroxyacetophenone with 2 equiv. of appropriate cinnamic acids in the presence of DCC and 4-PPy in dichloromethane at room temperature to afford the 2′,6′-dicinnamoyloxyacetophenones 39, which underwent cyclodehydration on treatment with potassium carbonate in dry pyridine at 120°C [13,82] or under MW irradiation [83] (Scheme 12).…”
Section: Baker-venkataraman Rearrangementmentioning
confidence: 99%
“…The reports found in literature deal with improvements of the most promising approaches, such as: 1) aldol condensation / oxidative cyclization [20][21][22][23][24][25][26] and 2) Baker-Venkataraman rearrangement. [26][27][28][29][30][31] Taking into consideration the important biological activities described for 2-styrylchromones (vide infra), it is advantageous if these compounds could be available by simple and efficient synthetic transformations. For that reason almost all reports on the synthesis of new 2-styrylchromones include their transformation and/or biological activities evaluations.…”
Section: Synthesis Of 2-styrylchromonesmentioning
confidence: 99%
“…28 The authors indicated that refluxing 2′-hydroxy-3′-allylacetophenones 23 (R = 3′-allyl) with cinnamoyl chlorides 24 (X =Cl) in potassium carbonate/acetone medium yields directly 1-(3-allyl-2-hydroxyaryl)-5-aryl-3-hydroxy-2,4-pentadien-1-ones 26 which were then cyclized in acid medium into 2-styrylchromones 27 (Scheme 6, steps A and B.i). More recently, the same research group has synthesized some 2-(2′-vinylthiophene)chromones 30 (2-styrylchromone-type compounds) in one step, by condensation of appropriate 2′,4′-dihydroxyacetophenones 28 and thiophene-2-acroyl chloride 29 (Scheme 7).…”
Section: Baker-venkataraman Rearrangementmentioning
confidence: 99%